Relating proton LETd to biological response of parotid and submandibular glands using PSMA-PET in clinical patients - Dirk Wagenaar; Vineet Mohan; Johannes A. Langendijk; Roel J.H.M. Steenbakkers; Wouter V. Vogel; Stefan Both (Clinical and Translational Radiation Oncology)
Background and purpose: A recent study investigated the use of PSMA-PET in monitoring loss of secretory cells in salivary glands of head and neck cancer (HNC) patients. Previously, a dose–effect relation has been formulated to the PSMA-PET uptake in salivary glands. The aim of this study was to derive a proton RBE model from the PSMA-PET uptake in salivary glands after proton therapy of HNC patients. Materials and methods: Six patients treated with proton therapy were included. These patients received a PET-CT scan using 68Ga (N = 1) or 18F (N = 5) PSMA before treatment (baseline) and one month after the last fraction (follow-up). Physical dose (D), D·LETd and the follow-up PSMA-PET scan were deformed to the baseline PET-CT using deformable image registration. Parotid and submandibular gland delineations were adjusted to include voxels which had an uptake of ≥ 5 g/ml in the baseline PSMA-PET scan. Results: The average RBE-LET slope was 0.075 [0.009; 0.125] (keV/μm)-1 (mean [95 %CI]) for parotid and submandibular glands combined. When analyzing parotid or submandibular glands separately the RBE-LET curve slope varies with two and five patients showing a positive RBE-LET slope when only analyzing parotid or submandibular glands respectively. Conclusion: Our study did not find clear evidence of an increased RBE in parotid and submandibular glands with increasing LETd. On average an LETd effect was observed, however our sample size was too small to clearly define an RBE-LET relation. A larger cohort scanned at later time intervals could shed more light on this issue.